2022
DOI: 10.1126/science.abq7684
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystals with metastable high-pressure phases under ambient conditions

Abstract: The ambient metastability of the rock-salt phase in well-defined model systems comprising nanospheres or nanorods of cadmium selenide, cadmium sulfide, or both was investigated as a function of composition, initial crystal phase, particle structure, shape, surface functionalization, and ordering level of their assemblies. Our experiments show that these nanocrystal systems exhibit ligand-tailorable reversibility in the rock salt–to–zinc blende solid-phase transformation. Interparticle sintering was used to eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…For another special example, Xiao et al found that suitable surface binding strength between amines and nanocrystals, as well as the ability of amine-capped nanocrystals to assemble into ordered superstructures, helped to retain the high pressure-induced metastable rock-salt (RS) phase of CdS (or CdSe) nanocrystals at ambient conditions. 26 For the CdS/CdSe nanocrystals capped with a mixture of oleylamine and cetyltrimethylammonium bromide, the pure RS phase obtained with compression could be fully preserved after decompression. As a typical kind of Cu-based semiconductor, Cu-based multicomponent semiconductor nanomaterials, such as Cu 2 ZnSnS 4 and Cu 2 ZnSn(S, Se) 4 , could crystallize in conventional tetragonal kesterite or stannite phases (in which all cations and anions are located separately in one fcc sublattice and stacked like the ZB structure), 27,28 and metastable hexagonal WZ phase.…”
Section: Typical Ligands For Phase Engineering Of Nanomaterialsmentioning
confidence: 95%
See 1 more Smart Citation
“…For another special example, Xiao et al found that suitable surface binding strength between amines and nanocrystals, as well as the ability of amine-capped nanocrystals to assemble into ordered superstructures, helped to retain the high pressure-induced metastable rock-salt (RS) phase of CdS (or CdSe) nanocrystals at ambient conditions. 26 For the CdS/CdSe nanocrystals capped with a mixture of oleylamine and cetyltrimethylammonium bromide, the pure RS phase obtained with compression could be fully preserved after decompression. As a typical kind of Cu-based semiconductor, Cu-based multicomponent semiconductor nanomaterials, such as Cu 2 ZnSnS 4 and Cu 2 ZnSn(S, Se) 4 , could crystallize in conventional tetragonal kesterite or stannite phases (in which all cations and anions are located separately in one fcc sublattice and stacked like the ZB structure), 27,28 and metastable hexagonal WZ phase.…”
Section: Typical Ligands For Phase Engineering Of Nanomaterialsmentioning
confidence: 95%
“…The amine ligands tended to adsorb on the surface of WZ-ZnS at lower temperatures and desorbed at higher temperatures, leading to the WZ-to-ZB phase transformation with increasing reaction temperature. For another special example, Xiao et al found that suitable surface binding strength between amines and nanocrystals, as well as the ability of amine-capped nanocrystals to assemble into ordered superstructures, helped to retain the high pressure-induced metastable rock-salt (RS) phase of CdS (or CdSe) nanocrystals at ambient conditions . For the CdS/CdSe nanocrystals capped with a mixture of oleylamine and cetyltrimethylammonium bromide, the pure RS phase obtained with compression could be fully preserved after decompression.…”
Section: Typical Ligands For Phase Engineering Of Nanomaterialsmentioning
confidence: 99%
“…Indeed, ligand effects on NC self-assembly and pressureinduced sintering processes have been utilized by Xiao et al to control kinetic barriers in NC phase transitions and fully preserve metastable high-pressure phases under ambient conditions. 111 For a given composition, a material can exist in various crystalline phases of different structures and properties, only one of which is often the thermodynamically most stable under ambient conditions. Kinetically trapping those higher energy phases (i.e., increasing the activation energy barrier of phase transitions) can potentially lead to metastable materials with new properties for emerging applications.…”
Section: Ligand Effectsmentioning
confidence: 99%
“…Colloidal nanocrystals (NCs), which serve as designable atoms, can spontaneously self-assemble into periodically ordered superlattices. Such superlattice solids, called “designer solids”, represent completely the new category of condensed matters, which not only can be used to explore the newly emergent properties at mesoscale , but also can be engineered into higher hierarchical materials. Upon discovery of collective properties from a variety of NC assembles, recent pressure engineering of such NC-ordering supercrystals has enabled 100% retention of high pressure metastable phases at ambient conditions . Such single NC supercrystals also display noticeable anisotropy of collective property as superlattices change in space symmetry and crystallographic orientation. In order to make better use of such unique properties and further enable fine-tuning and controllable engineering of such supercrystals, it is crucial to explore and find ways of designable control of NC assembly environments to grow large free-standing 3D single supercrystals with desired superlattices.…”
Section: Introductionmentioning
confidence: 99%
“…6−9 Upon discovery of collective properties from a variety of NC assembles, recent pressure engineering of such NC-ordering supercrystals has enabled 100% retention of high pressure metastable phases at ambient conditions. 10 Such single NC supercrystals also display noticeable anisotropy of collective property as superlattices change in space symmetry and crystallographic orientation. 11−14 In order to make better use of such unique properties and further enable fine-tuning and controllable engineering of such supercrystals, it is crucial to explore and find ways of designable control of NC assembly environments to grow large free-standing 3D single supercrystals with desired superlattices.…”
Section: ■ Introductionmentioning
confidence: 99%